The Interpretation of Gregor's Transformation in The Metamorphosis from the Perspective of Existentialism - Anheng, Li (Bohemistyka, 2022)
The Metamorphosis is one of the greatest novels written by Franz Kafka in 1915, which depicts the surreal and absurd transformation of Gregor Samsa into a beetle. Existentialism is borrowed to help interpret the implications of Gregor's transformation. After the transformation, Gregor lives in hatred, dread, absurdity, hopelessness, helplessness and despair. He is isolated, estranged, alienated by his family and the society. Centering on Gregor's transformation, this paper discovers that the authentic existing situation of the underprivileged is entirely revealed in this novella; the pathetic dark side of the human existence is vividly depicted and presented via transformation by Franz Kafka, who meanwhile deeply explores the negative sensations of human existence.